PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN BERFIKIR KRITIS PESERTA DIDIK PADA MATA PELAJARAN GEOGRAFI KELAS XI IPS DI SMA PERTIWI 1 PADANG - Saputri, Elza Yulian; Suasti, Yurni (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
The purpose of the study was to determine the effect of the Problem Based Laerning (PBL) model on students' critical thinking skills in class XI social studies geography subjects at SMA Pertiwi 1 Padang. Samples are taken by purposive sampling, which is based on the same number of students. Each control class (XI IPS 2) numbered 36 people and the experimental class (XI IPS 3) amounted to 36 people. The data was collected through a test consisting of five critical thinking indicators proposed by Ennis. This study found a significant influence on the use of the Problem Based Learning (PBL) model on students' critical thinking skills in geography subjects. Evidenced by the results of the hypothesis test (t test) obtained Tcalculate (8.69) > Ttable (1.99) with a significant level of α = 0.05. Strengthened by the results of N Gain, the experimental class score of 0.71 is in the high category and the control class is 0.36 in the medium category. Keywords : Problem Based Learning (PBL), Experimen, Critical Thinking